2020
DOI: 10.1007/s00595-020-02111-6
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of infectious complications using C-reactive protein and the procalcitonin levels after laparoscopic colorectal resection: a prospective cohort study

Abstract: Purpose The predictive values of the C-reactive protein (CRP) and procalcitonin (PCT) levels for postoperative infectious complications were investigated in patients who underwent elective laparoscopic resection of colorectal cancer. Methods A total of 154 consecutive patients who underwent elective laparoscopic resection for colorectal cancer (CRC) were prospectively studied. The CRP and PCT levels on the first postoperative day (POD1) and the fourth postoperative day (POD4) were measured. Any correlations be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
(40 reference statements)
1
5
0
1
Order By: Relevance
“…0%) developed ICs after surgery for CRC, which is comparable to multiple previous studies[24][25][26][27]. Furthermore, chronic pulmonary diseases, diabetes mellitus, preoperative and/or intraoperative blood transfusion, and longer operation time were identified as independent risk factors for ICs.…”
supporting
confidence: 85%
“…0%) developed ICs after surgery for CRC, which is comparable to multiple previous studies[24][25][26][27]. Furthermore, chronic pulmonary diseases, diabetes mellitus, preoperative and/or intraoperative blood transfusion, and longer operation time were identified as independent risk factors for ICs.…”
supporting
confidence: 85%
“…In their study of 154 patients, Tatsuoka et al found that PCT 4th POD has higher specificity and sensitivity than CRP values in patients with dehiscence of colorectal anastomosis. 24 Besides, Takakura et al in their study confirmed PCT as an important prognostic marker of anastomotic leakage in patients operated on for colorectal cancer. 25 In this study, which included 118 patients operated on colorectal cancer, it was found that all patients with anastomotic leakage had a significant increase in PCT values on the second and fourth day compared to patients without anastomotic leakage.…”
Section: Discussionmentioning
confidence: 93%
“…The lack of a clear understanding of the pathophysiology behind AL led to the diversification of the investigated potential biomarkers across broad categories such as those of inflammation, ischemia, and tissue repair [ 11 ]. Although none of the examined biomarkers proved to be the gold standard, CRP shows promising results in contemporary literature [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%